Free-roaming dog populations and movement methodologies for global rabies elimination: knowns and unknowns – a scoping review - Cunha Silva, Laura; Fellenberg, Constanza; Freudenthal, Jerónimo; Tiwari, Harish Kumar; Dürr, Salome (Frontiers in Veterinary Science, 2025)
Understanding free-roaming dog (FRD) demographics and movement patterns is essential for effective rabies control interventions, such as mass dog vaccinations (MDV). This review assesses published studies on FRD movement and enumeration to assess existing knowledge. A scoping review was conducted following PRISMA guidelines. Three databases, namely, Embase, Scopus, and Web of Science databases, were searched for publications between 2012 and 2024. A total of 2,167 articles were screened through successive filtration process to select a final corpus of 52 publications. The studies were predominantly from India (n = 8), Brazil (n = 6), Indonesia (n = 5), Guatemala (n = 5) and Chad (n = 5) and mostly investigated FRD population size. Several techniques were used for FRD enumeration, with photographic mark capture-recapture being the most common. Most FRD movement studies focused on home ranges, influenced by the technique and population size. In many studies, advantages and disadvantages of the techniques employed remained unreported, leaving a scope for misleading conclusions when comparing the methods used. The review highlights significant research gaps in FRD movement and population studies in rabies-endemic regions, which are often overlooked in rabies control strategies. Addressing these gaps through targeted research is essential for developing more effective, evidence-based interventions.